THE RELATIONSHIP BETWEEN BEHAVIOR OF USING REPEATED COOKING OILS AND RECURRENCE OF HYPERTENSION - Sari, Mella Novika; Rohmawati, Dhian Luluh (Journal of Vocational Nursing, 2021)
Introduction: Hypertension is an abnormal increase in systolic blood pressure of more than 140 mmHg and diastolic more than 90 mmHg. Hypertension cannot be cured as a whole, therefore hypertension can recur. One of the factors in the occurrence of recurrence is the use of repeated cooking oil. Repeated cooking oil is cooking oil that has been used repeatedly more than once. The aim of this research to determine the relationship between the behavior of repeated use of cooking oil and the recurrence of hypertension. Methods: The design repeated is correlation with cross sectional approach. The sampling technique was carried out by purposive sampling with a sample size of 82 respondents. Collecting data using a questionnaire instrument with data processing using the T-score and Chi Square statistical test. The results of this study found that 47 respondents (57.3%) behaved using repeated cooking oil and found that 42 respondents (51.2%) experienced frequent recurrence of hypertension. Result: The results showed a significant relationship between the behavior of using repeated cooking oil and the recurrence rate of hypertension (p = 0.002). Conclusion: Further researchers need to be investigated related to nutritional pattern factors, smoking history, stress and others. In addition, it can be researched regarding the knowledge of the dangers of using repeated cooking oil for health.